1983
DOI: 10.1227/00006123-198306000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hypertension and Prophylaxis against Vasospasm in Cases of Subarachnoid Hemorrhage: A Preliminary Report

Abstract: Thirty hypertensive patients with subarachnoid hemorrhage were divided randomly into two groups. The treated group was begun on preliminary volume expansion, and control of hypertension was carried out using vasodilators and centrally acting drugs. The control group was treated in the classical manner for hypertension, with a diuretic as the foundation for therapy. The incidence of clinical vasospasm was compared to that of angiographic spasm. The incidence of preoperative vasospasm in the treated group was 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 0 publications
1
31
0
2
Order By: Relevance
“…Because of its delayed onset, this complication is often called delayed cerebral ischemia (DCI). 2,4 Besides the term "DCI," many other terms are used in the literature to describe this clinical phenomenon, such as delayed ischemic neurological deficit, [5][6][7] delayed ischemic deficit, 8,9 delayed neurological deficit, 10,11 secondary cerebral ischemia, 12,13 vasospasm, 14,15 clinical vasospasm, 16,17 symptomatic vasospasm, 18,19 symptomatic ischemia, 20 and cerebral infarction. 21 The use of so many different terms is problematic, not only because many studies provide incomplete definitions of the terms used, if at all, 22,23 but also because a variety of definitions are used for the same term.…”
mentioning
confidence: 99%
“…Because of its delayed onset, this complication is often called delayed cerebral ischemia (DCI). 2,4 Besides the term "DCI," many other terms are used in the literature to describe this clinical phenomenon, such as delayed ischemic neurological deficit, [5][6][7] delayed ischemic deficit, 8,9 delayed neurological deficit, 10,11 secondary cerebral ischemia, 12,13 vasospasm, 14,15 clinical vasospasm, 16,17 symptomatic vasospasm, 18,19 symptomatic ischemia, 20 and cerebral infarction. 21 The use of so many different terms is problematic, not only because many studies provide incomplete definitions of the terms used, if at all, 22,23 but also because a variety of definitions are used for the same term.…”
mentioning
confidence: 99%
“…Eleven original studies dealing with prophylactic hypervolemic therapy after aneurysmal SAH were identified: four randomized controlled trials (RCTs), two prospective interventional trials, and five observational series using historic controls (Table 1) [2][3][4][7][8][9][10][11][12][13][14]. Together, the RCTs included 244 patients; data from another 531 patients were investigated in the remaining studies.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…Rosenwasser and colleagues [7] investigated 30 patients after aneurysmal SAH grade I to IV on the Hunt-Hess scale, divided randomly in two groups. The treatment group received a pulmonary artery catheter and volume loading with albumin up to a pulmonary capillary wedge pressure (PCWP) of 12-15 mm Hg; this group also received a complex medication regimen, including hydralazine, methyldopa, propranolol, and nitroprusside to keep the systolic blood pressure below 120 mm Hg.…”
Section: Randomized Trialsmentioning
confidence: 99%
“…Therapeutic manipulation of hemodynamics and blood rheology for the supportive management of vasospasm was first described 30 years ago (Kosnik and Hunt, 1976;Rosenwasser et al, 1983). The combination of induced hypertension, hypervolemia, and hemodilution (HHH) therapy is widely used for prophylaxis and therapy in the setting of angiographic or clinical vasospasm (Brisman et al, 2006;Mayberg et al, 1994;Sakowitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The hemodilution aspect of HHH therapy continues to be controversial (Awad et al, 1987;Ekelund et al, 2002;Hassan et al, 2004;Kosnik and Hunt, 1976;Muench et al, 2007;Naidech et al, 2007;Rosengart et al, 2007;Rosenwasser et al, 1983;Treggiari et al, 2003). In spite of this, it is practiced 30% to 60% of the time (Meyer et al, 2011;Sakowitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%